Boldine protects endothelial function in hyperglycemia-induced oxidative stress through an antioxidant mechanism - Lau, Y.S.; Tian, X.Y.; Huang, Y.; Murugan, D.; Achike, F.I.; Mustafa, Mohd Rais (Elsevier, 2012)
Increased oxidative stress is involved in the pathogenesis and progression of diabetes. Antioxidants are therapeutically beneficial for oxidative stress-associated diseases. Boldine (s-2,9-dihydroxy-1,10-dimethoxyaporphine) is a major alkaloid present in the leaves and bark of the boldo tree (Peumus boldus Molina), with known an antioxidant activity. This study examined the protective effects of boldine against high glucose-induced oxidative stress in rat aortic endothelial cells (RAEC) and its mechanisms of vasoprotection related to diabetic endothelial dysfunction. In RAEC exposed to high glucose (30 mM) for 48 h, pre-treatment with boldine reduced the elevated ROS and nitrotyrosine formation, and preserved nitric oxide (NO) production. Pre-incubation with Î²-NAPDH reduced the acetylcholine-induced endothelium-dependent relaxation; this attenuation was reversed by boldine. Compared with control, endothelium-dependent relaxation in the aortas of streptozotocin (STZ)-treated diabetic rats was significantly improved by both acute (1 Î¼M, 30 min) and chronic (20 mg/kg/daily, i.p., 7 days) treatment with boldine. Intracellular superoxide and peroxynitrite formation measured by DHE fluorescence or chemiluminescence assay were higher in sections of aortic rings from diabetic rats compared with control. Chronic boldine treatment normalized ROS over-production in the diabetic group and this correlated with reduction of NAD(P)H oxidase subunits, NOX2 and p47phox. The present study shows that boldine reversed the increased ROS formation in high glucose-treated endothelial cells and restored endothelial function in STZ-induced diabetes by inhibiting oxidative stress and thus increasing NO bioavailability.